Post-war experiences with developmental central banks : the good, the bad and the hopeful - Epstein, Gerald (UN New YorkUS, 2009)
Describes some simple statistical attempts to assess on a comparative basis the impact of developmental central banking on economic growth. Presents some case studies on developmental central banks in developing countries. Provides some concrete alternatives on how developmental central banks can implement a more socially useful approach to central banking, including tools for protecting developing economies from financial instability.